KETERKAITAN WHITE COLLAR CRIME DENGAN CORPORATE CRIME - R. Dyatmiko Soemodihardjo (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
White collar crime is a crime that carried out by respected persons, whereas corporate crime is a crime that related to corporation. White collar crime and crime corporate are always related to economic crime. White collar crime can be committed by corporation, that is why a kind of crime emerges namely corporate crime.